The Influence of Jigsaw Technique on Students' Reading Comprehension of Narrative Texts at Insan Madani Susoh Middle School - Karmissa Azkya; Nuzulul Isna (Jurnal Pustaka Cendekia Pendidikan, 2026)
Although reading comprehension is vital in English learning, many students still struggle with narrative texts.This study examined how the Jigsaw technique affects narrative reading comprehension at SMP IT Insan Madani Susoh. Using a quantitative, pre-experimental one-group pre-test and post-test design, the research involved 60 purposely selected eighth-grade students.Data were collected via a multiple-choice reading test before and after the treatment to assess students' ability to identify main ideas, detailed information, vocabulary, events sequence, and moral values.The results showed a significant increase in the students' mean score from 57.50 to 80.25, while those meeting the Minimum Passing Criteria rose from 16.67% to 90%. Statistical analysis confirmed the data were normally distributed, and a Paired Samples t-test revealed a significant difference between pre-test and post-test scores (Sig. 2-tailed < 0.001). Additionally, the average N-Gain was 0.5529, classified as moderate. Thus, the Jigsaw technique effectively improves students' narrative reading comprehension and is highly recommended for junior high school classrooms